BUILDING THE IMAGE OF A “CITRA ANAK BANGSA”: A RETROSPECTIVE STUDY OF PTDI N219’S PUBLIC RELATIONS MANAGEMENT - Muhammad Reza Panangian; Andreas Dion Anggoro (Jurnal Visi Komunikasi, 2026)
This study aims to retrospectively evaluate PT Dirgantara Indonesia’s (PTDI) public relations (PR) management in constructing the image of the N219 aircraft as a “Karya Anak Bangsa” during the initiation phase in 2019, as well as its impact on the product’s reputation in 2026. Using a qualitative approach with a single-case study method, this study examines the implementation of the Planning, Organizing, Actuating, and Controlling (POAC) management functions through in-depth interviews, observations, and document analysis. The findings reveal that despite inter-institutional coordination challenges and limited publication budgets, the PR role as an Expert Prescriber—prioritizing physical validation through aerospace exhibitions—proved pivotal in building long-term market trust. This study reveals the existence of an Efficiency Paradox, wherein cost-efficient digital channels are not always effective in mitigating socio-psychological skepticism toward domestic high-tech products when compared to direct physical interactions. Theoretically, this study contributes to the development of Excellence Theory by emphasizing the importance of validating communication in high-risk manufacturing industries. The research findings recommend the need for a single voice policy across institutions to strengthen public loyalty toward national strategic innovations.